Priming iTBS for lower limb rehabilitation after stroke: Protocol for a randomized controlled trial on efficacy and neuroplasticity - Zhipeng Pan; Jianxia Lu; Yue Sun; Yao Qian; Yi Shao; Chengchen Chen; Hongrui Liu; Jianchen Zhang; Zixuan Huang; Limin Sun; Kewei Yu; Ya Zhou; et al. (PLoS ONE, 2026)
Introduction Repetitive transcranial magnetic stimulation (rTMS) is widely applied in treating motor dysfunction after stroke. Building on metaplasticity principle, continuous theta burst stimulation (cTBS) preconditioning enhances subsequent excitatory effects of intermittent theta burst stimulation (iTBS). This phenomenon is well-established for upper limbs in healthy populations, yet its application to the lower limbs remains underexplored, especially in stroke survivors. Guided by “central-peripheral-central” theory, this protocol investigates the synergistic effects of cTBS-preconditioned iTBS combined with lower limb robotic exoskeleton training for functional recovery and neuroplasticity after stroke. Methods and analysis This single-blind, three-arm randomized controlled trial will assess the effects of priming iTBS combined with REX exoskeleton training in subacute stroke patients. Participants (n = 60) will be randomly assigned 1:1:1 to: (1) priming (cTBS + iTBS), (2) non-priming (sham cTBS + iTBS), or (3) sham stimulation (sham cTBS + sham iTBS). Stimulation targets lower-limb primary motor cortex (M1) using a double-cone coil (80% active motor threshold). All groups will receive REX exoskeleton training as conventional therapy to facilitate sensorimotor loop integration through proprioceptive feedback. The intervention lasts for 4 weeks, with assessments at baseline, mid-intervention, post-intervention, and 6-week follow-up. Primary outcome is the Fugl-Meyer Assessment of Lower Extremity (FMA-LE) score. Secondary outcomes include the Postural Assessment Scale for Stroke (PASS), Modified Barthel Index (MBI), and three-dimensional gait analysis, complemented by surface electromyography (sEMG) to assess muscle activation patterns and coordination during functional movements. The functional near-infrared spectroscopy (fNIRS) functional connectivity, motor evoked potential (MEP) indices, and electroencephalography (EEG) signals will be analyzed to explore the neural plasticity underlying the treatment effects. Data will be analyzed using mixed-design analysis of variance (ANOVA), and the study achieves 90% power to detect FMA-LE differences with 20 participants per group.